Antioxidant activities of enzymatic‐hydrolysed proteins of dromedary (Camelus dromedarius) colostrum. (6th November 2019) - Oussaief, Olfa; Jrad, Zeineb; Adt, Isabelle; Dbara, Mohamed; Khorchani, Touhami; El‐Hatmi, Halima
Abstract : This work investigated the antioxidant activities of dromedary colostrum proteins before and after hydrolysis by pepsin, trypsin, α‐chymotrypsin, pancreatin and papain. The enzymatic hydrolysis affected the degrees of hydrolysis, electrophoretic profiles, molecular weight distribution and hydrophobic/hydrophilic properties of the generated peptides. The antioxidant activities were evaluated using four antioxidant assays, including 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) and 2, 2′‐azinobis(3‐ethylbenzothiazoline‐6‐sulfonic acid) (ABTS) radical‐scavenging activities, ferric reducing power and ferrous ion chelating activity. Interestingly, the antioxidant activities of dromedary colostrum proteins were enhanced after enzymatic hydrolysis. The highest antioxidant potential was obtained by pancreatic hydrolysates ( P  ≤ 0.05). These results suggest that dromedary colostrum protein hydrolysates are an important source of natural antioxidant peptides.